2012
DOI: 10.1088/0264-9381/29/9/095016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced basis representations of multi-mode black hole ringdown gravitational waves

Abstract: We construct compact and high accuracy Reduced Basis (RB) representations of single and multiple quasinormal modes (QNMs). The RB method determines a hierarchical and relatively small set of the most relevant waveforms. We find that the exponential convergence of the method allows for a dramatic compression of template banks used for ringdown searches. Compressing a catalog with a minimal match MM = 0.99, we find that the selected RB waveforms are able to represent any QNM, including those not in the original … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 50 publications
1
55
0
Order By: Relevance
“…A variety of ROM-type techniques have recently appeared in the GW literature [10,[12][13][14][15][16][17]. We shall use a combination of the reduced-basis method and the empirical interpolation method, whose favorable computational efficiency, ease-of-parallelization and numerical stability make them attractive candidates for tackling precessing waveform systems and other challenging models.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ROM-type techniques have recently appeared in the GW literature [10,[12][13][14][15][16][17]. We shall use a combination of the reduced-basis method and the empirical interpolation method, whose favorable computational efficiency, ease-of-parallelization and numerical stability make them attractive candidates for tackling precessing waveform systems and other challenging models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [39][40][41][42] has shown that for fixed but arbitrary physical and parameter ranges, a small number of basis functions is indeed sufficient to accurately represent any waveform of the same physical model and with an exponentially decaying greedy error (9). Such observations are expected for functions with smooth parameter dependence, as is the case with gravitational waveforms.…”
Section: Surrogate Model Buildingmentioning
confidence: 97%
“…whereas waveforms from T (even if not in the training set) continue to be well approximated by the RB if the training set is dense enough [39][40][41][42]. Since the waveform space is numerically finite dimensional [39], one can verify sufficiently dense training sets through convergence as M gets larger or by checking how well the basis represents randomly selected waveforms (see Appendix A).…”
Section: Surrogate Model Buildingmentioning
confidence: 99%
See 2 more Smart Citations